PERAN KUALITAS LAYANAN, CITRA PERUSAHAAN DAN KEPERCAYAAN TERHADAP LOYALITAS PASIEN RAWAT JALAN RUMAH SAKIT HERMINA KENDARI (Role Of Service Quality, Company Image And Trust In Patient Loyalty Hermina Kendari Hospital) - Eka Maya Sari; Juharsah Juharsah; Wahyuniati Hamid (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2022)
This studi aims to: 1)examine the simultaneous effect of service quality, hospital image and trust on outpatient loyalty, 2)examine the effect of service quality on outpatient loyalty, 3)examine the effect of hospital image on outpatient loyalty, 4) examine the effect of trust on outpatient loyalty. The object of research is the Hermina Kendari Hospital. The research population is the outpatients of Hermina Kendari Hospital totalling 7.928 respondents. The sampling technique uses the Slovin formula with a precision of 10 percent, thuse research sample is 100 respondents. The data collection method used a questionnaire and all samples returned the submitted questionnaire. The research data was processed using multiple linear regression analysis using the SPSS Ver 24 device.The result of study: 1)simultaneously service qualility, hospital image and trust have a positive and significant effect on outpatient loyalty, 2)service quality has a positive and significant effect on outpatient loyalty, 3)hospital image has a positive and significant effect on outpatient loyalty, 4)trust has a positive and significant effect on outpatient loyalty